2013
DOI: 10.1016/j.ijgo.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal sleep practices with pre‐eclampsia, low birth weight, and stillbirth among Ghanaian women

Abstract: Objective To assess sleep practices, and investigate their relationship with maternal and fetal outcomes, among pregnant Ghanaian women. Methods In a cross-sectional study conducted at Korle Bu Teaching Hospital, Accra, Ghana, between June and July 2011, postpartum women were interviewed within 48 hours of delivery about sleep quality and practices during pregnancy. Interviews were coupled with a systematic review of participants’ medical charts for key outcomes including maternal hypertension, pre-eclampsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 24 publications
9
92
1
1
Order By: Relevance
“…97 The adverse effect of supine sleep position in late pregnancy has been emphasised as a potentially modifiable risk factor for stillbirth. [98][99][100][101] Although these findings are biologically plausible, results from further studies in the UK 102 and New Zealand 99 study are awaited.…”
Section: Promising Antenatal Interventions?mentioning
confidence: 99%
“…97 The adverse effect of supine sleep position in late pregnancy has been emphasised as a potentially modifiable risk factor for stillbirth. [98][99][100][101] Although these findings are biologically plausible, results from further studies in the UK 102 and New Zealand 99 study are awaited.…”
Section: Promising Antenatal Interventions?mentioning
confidence: 99%
“…Other, smaller studies of snoring and hypertension have also demonstrated such a relationship [17][18][19]. In a study of n = 209 women, compared to non-snorers, women who reported snoring in the first trimester had an OR of 4.0 (95%CI 1.3-11.9) for developing gestational hypertension [18].…”
Section: Gestational Hypertension/preeclampsiamentioning
confidence: 92%
“…63 A study of stillbirth at ≥32 weeks' gestation reported 6.24 increased risk of stillbirth for supine sleep compared with the left side. 64 Although the mechanisms underlying this association have yet to be delineated, growth restriction is more prevalent in stillbirths of women reporting sleeping on the back, 65 indicating a potential role of uterine blood flow.…”
Section: Fetal Infant and Maternal Physiologymentioning
confidence: 99%